2014
DOI: 10.3390/ani4040612
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira spp. in Domestic Cats from Different Environments: Prevalence of Antibodies and Risk Factors Associated with the Seropositivity

Abstract: Simple SummaryAlthough Leptospira infection occurs in domestic cat populations, studies on leptospirosis are very limited in felines and the role of cats in the epidemiology of this zoonosis has not received much attention. The present work is an epidemiologic study intended to determine the prevalence of anti-Leptospira antibodies and risk factors related with the seropositivity in cats from urban and rural environments. A higher prevalence in rural cats was detected (25.2%) compared with urban animals (1.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 26 publications
4
44
1
1
Order By: Relevance
“…Seroprevalence against Leptospira observed in our study (4.1% positive 95% CI: 2.1-7.18%), fell within the previous intervals described worldwide, 4% to 33.3% [14,16,17,37]. Environmental factors such as outdoor habits, presence of farm animals that may shed leptospires in the neighborhood, prey habits, or even the season of the year (resulting in different levels of exposure to pathogenic leptospires), can explain the broad ranges of antibody prevalence reported in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Seroprevalence against Leptospira observed in our study (4.1% positive 95% CI: 2.1-7.18%), fell within the previous intervals described worldwide, 4% to 33.3% [14,16,17,37]. Environmental factors such as outdoor habits, presence of farm animals that may shed leptospires in the neighborhood, prey habits, or even the season of the year (resulting in different levels of exposure to pathogenic leptospires), can explain the broad ranges of antibody prevalence reported in the literature.…”
Section: Discussionsupporting
confidence: 88%
“…Clinical presentation of the disease is rare and usually mild in cats [9][10][11][12]. Several studies in different geographical areas have demonstrated that cats have contact with Leptospira since they develop specific antibodies ranging from 4% to 33.3%, with no clear association to clinical disease [13][14][15][16][17]. Urinary shedding of Leptospira DNA has also been documented in cats, with a prevalence ranging up to 67.8% depending on various factors including the geographical area, the presence in the area of farm animals infected with leptospires, and prey habits [7,14,15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, gender and reproduction status were not significantly associated with Leptospira infection as described in earlier studies (Azocar‐Aedo, Monti, & Jara, ; Brasil de Lima et al., ; Larsson et al., ; Mosallanejad et al., ; Mylonakis et al., ; Rodriguez et al., ). Environmental factors also did not influence the risk of a Leptospira infection, although it would be expected that cats living in rural areas have a higher risk (Azocar‐Aedo et al., ). Most of the cats (207/260) were sampled in urban areas, but the percentage of positive cats in urban and rural areas was identical (6.3%).…”
Section: Discussionsupporting
confidence: 81%
“…Cats may shed as much Leptospira as dogs do [41,42]. Therefore, cats can be a source of urban leptospirosis [38,[42][43][44], and in this case, the patient's cat may have been a potential infection source.…”
Section: Discussionmentioning
confidence: 99%